The contribution of an avian top predator to selection in prey species. - Vedder, O; Bouwhuis, S; Sheldon, B (2014)
Natural selection can vary in magnitude, form and direction, yet the causes of selection, and of variation in selection, are poorly understood. We quantified the effect of a key predator (Eurasian sparrowhawks) on selection on fledging body mass in two bird species (blue tits and great tits). By partitioning selection into within- and between-brood components, we were able to separate individual from brood-level effects of fledging mass on predation probability and recruitment. In blue tits, selection on fledging mass by sparrowhawk predation was nonsignificant and could not explain selection to recruitment. In contrast, in great tits, sparrowhawk predation selected for increased fledging mass at the individual level and could explain 73% of individual-level selection on fledging mass to recruitment. Moreover, in great tits, individual-level selection on fledging mass was significantly stronger in years in which sparrowhawks were present compared to years when sparrowhawks were absent. Selection at the brood level was independent of sparrowhawk presence. These results provide compelling evidence that sparrowhawk predation acts as an important causal agent of selection on fledging mass in great tits but not in blue tits. Variation in predation pressure can therefore account for variation in selection, but specific patterns may not be easily generalized across species.